2017
DOI: 10.1186/s40793-017-0249-z
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome sequence of the cold adapted crude-oil degrader: Pedobacter steynii DX4

Abstract: Pedobacter steynii DX4 was isolated from the soil of Tibetan Plateau and it can use crude oil as sole carbon and energy source at 15 °C. The genome of Pedobacter steynii DX4 has been sequenced and served as basis for analysis its metabolic mechanism. It is the first genome of crude oil degrading strain in Pedobacter genus. The 6.58 Mb genome has an average G + C content of 41.31% and encodes 5464 genes. In addition, annotation revealed that Pedobacter steynii DX4 has cold shock proteins, abundant response regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…At the class level, phylum Bacteroidetes was mainly represented by Sphingobacteriia, whose shift in relative abundance followed the trend observed for Bacteroidetes ( Figure 2 and Supplementary Table S6 ). The higher abundances of Sphingobacteriia in oil can be supported by the fact that many of the affiliated members of Sphingobacteriia can degrade oil, thus making them appropriate members of the bacterial community in OWCs ( Szabó et al, 2011 ; Noparat et al, 2014 ; Chang et al, 2017 ). Moreover, a previous study has also reported the presence of Sphingobacteriia as a part of an oil-degrading bacterial community ( Liu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the class level, phylum Bacteroidetes was mainly represented by Sphingobacteriia, whose shift in relative abundance followed the trend observed for Bacteroidetes ( Figure 2 and Supplementary Table S6 ). The higher abundances of Sphingobacteriia in oil can be supported by the fact that many of the affiliated members of Sphingobacteriia can degrade oil, thus making them appropriate members of the bacterial community in OWCs ( Szabó et al, 2011 ; Noparat et al, 2014 ; Chang et al, 2017 ). Moreover, a previous study has also reported the presence of Sphingobacteriia as a part of an oil-degrading bacterial community ( Liu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pedobacter is a ubiquitous genus of soil bacteria that has been isolated from all over the world. These microbes may be especially relevant because some members of this genus are capable of crude oil degradation (Chang et al, 2017). Microbes that can degrade crude oil may be more able to degrade complex organic molecules like cyclo-alkanes in carbonaceous chondrites.…”
Section: Bacterial and Archaeal Sequencingmentioning
confidence: 99%